2021
DOI: 10.3390/life11040275
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Correlates of Small Animal Phobia in Human Subjects through fMRI: The Role of the Number and Proximity of Stimuli

Abstract: Brain regions involved in small-animal phobia include subcortical and cortical areas. The present study explored the neuronal correlates of small-animal phobia through fMRI data to determine whether a manipulation of number and proximity parameters affects the neurobiology of the processing of feared stimuli. The participants were 40 individuals with phobia and 40 individuals without phobia (28.7% male and 71.3% female). They watched videos of real and virtual images of spiders, cockroaches and lizards in moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The third study (Petrescu et al, 2020), in turn, found that anxiety levels during height exposure may be predicted using features extracted from heart rate and skin conductance measurements. A series of fMRI studies in small animal phobia showed that VR exposure leads to activations of fear-related brain areas (Clemente et al, 2014), that the intensity of brain activation and number of structures involved is higher in phobics than HC (Fumero et al, 2021), that 3D animated animal stimuli (spiders, lizards, cockroaches) elicit anatomically-similar (but weaker) brain activations as photorealistic 3D videos showing the same animals in persons with SP (Peñate et al, 2019), and that a higher number and greater proximity of fear related stimuli increases the neuronal phobic response (Fumero et al, 2021).…”
Section: Assessment Studiesmentioning
confidence: 99%
“…The third study (Petrescu et al, 2020), in turn, found that anxiety levels during height exposure may be predicted using features extracted from heart rate and skin conductance measurements. A series of fMRI studies in small animal phobia showed that VR exposure leads to activations of fear-related brain areas (Clemente et al, 2014), that the intensity of brain activation and number of structures involved is higher in phobics than HC (Fumero et al, 2021), that 3D animated animal stimuli (spiders, lizards, cockroaches) elicit anatomically-similar (but weaker) brain activations as photorealistic 3D videos showing the same animals in persons with SP (Peñate et al, 2019), and that a higher number and greater proximity of fear related stimuli increases the neuronal phobic response (Fumero et al, 2021).…”
Section: Assessment Studiesmentioning
confidence: 99%
“…Different therapeutic components of CBT may activate different neural substrates, which would indicate that there is more than one mechanism explaining CBT efficacy. Some studies suggest that exposure to phobic stimuli can be altered by contextual conditions, such as proximity to stimuli or real or virtual images [ 15 , 21 ]. These different conditions imply changes in brain activation or deactivation areas and in turn affect CBT efficacy [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, common and specific factors have been identified with the various diagnoses related to anxiety to the extent that different features of the phobic stimulus activate different brain areas. Thus, stimuli presenting near activated areas were associated with a motor response, whereas a greater number of phobic stimuli activated sensory areas [ 15 ], suggesting a different emotion regulation strategy.…”
Section: Introductionmentioning
confidence: 99%